2020
DOI: 10.9770/jesi.2020.7.4(16)
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate governance mechanism on the integrated financial reporting and investment risk of Thai listed companies

Abstract: This study was to examine relationships between corporate governance mechanism, integrated financial reporting, and investment risk on the stock exchange in Thailand. This study has investigated determinants and consequences of integrated financial reporting by analyzing Form 56-1 for year-end 2015 of the 240 Thai listed firms. To examine the relationship, an integrated financial reporting checklist was developed to identify the level of integrated reporting of listed firms on the Stock Exchange of Thailand. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The number of institution-owned companies, the board size, and CSR award recipients all had a significant positive relationship with the degree of integrated reporting. Chanatup et al (2020) investigated the links between corporate governance mechanisms, integrated financial reporting, and investment risk in the Thai stock market. The research discovered a favorable connection between stakeholder-oriented corporate governance structures and integrated financial reporting.…”
Section: Corporate Governance and Information Disclosurementioning
confidence: 99%
“…The number of institution-owned companies, the board size, and CSR award recipients all had a significant positive relationship with the degree of integrated reporting. Chanatup et al (2020) investigated the links between corporate governance mechanisms, integrated financial reporting, and investment risk in the Thai stock market. The research discovered a favorable connection between stakeholder-oriented corporate governance structures and integrated financial reporting.…”
Section: Corporate Governance and Information Disclosurementioning
confidence: 99%
“…The investors from the USA and Germany prefer to choose the enterprises with higher social responsibility level when making personal investment decisions or making recommendations even though they know that this might mean lower return on investments, since they believe that activities carried out by such socially responsible enterprises are beneficial for society. The enterprises whose management is oriented towards stakeholders and seeing that social responsibility level has an impact on investors are likely to disclose more information about the business, especially its policies regarding social and environmental responsibility (Chanatup, Aujirapongpan, Ritkaew, 2020).…”
Section: Conflict Between the Creative Accounting And The Corporate Social Responsibility The Impact On The Reliability Of Information Anmentioning
confidence: 99%
“…Yet the financial reporting of the enterprise is unreliable and incorrect because of the creative accounting which may mislead the stakeholders or they might even incur losses because of this. The study by Chanatup, Aujirapongpan, Ritkaew (2020) showed that the enterprises where management is oriented towards the shareholders and which consider maintaining benefits for them a priority, the financial accountability has a positive connection with the risk of investment, which means that the information an enterprise presents might have an impact on the investors' confidence in the enterprise and affect their behaviour. Moreover, the study by Arnold et al (2017) shows that the enterprise which manipulates the information presented in the financial statements, can deliberately shift the attention of the investors towards specific information that is beneficial only to the enterprise and on the basis of which, investors will make their decisions.…”
Section: Conflict Between the Creative Accounting And The Corporate Social Responsibility The Impact On The Reliability Of Information Anmentioning
confidence: 99%
“…Although several recent studies have investigated the relationship between board characteristics (i.e., size, independence, gender diversity, meetings, age, and education) and IR disclosure quantity and/or quality, these studies largely considered developed countries [4,5,19,34,35]. However, little research has investigated this relationship in emerging and developing markets [36,37]. To the best of the researchers' knowledge, no comprehensive study has investigated the board's role in determining IR disclosure quantity and quality in Malaysia.…”
Section: Introductionmentioning
confidence: 99%